The Sun about Heliocentric Theory in Science Perspective and Al-Qur'an Tafsir al-Maraghi - Umul Jazila; Suliyanah Suliyanah (Al-Hayat: Journal of Islamic Education, 2020)
This study aims to analyze the sun as the centre of the solar system in the heliocentric theory from the point of view of physics and the Qur'an. The research method used is a qualitative research method with library research (Library Research). The results of this study are proof of the truth that in the Qur'an, there is also a science that explains the heliocentric theory, which states that the sun is the centre of the solar system. Based on the idea of Nicolaus Copernicus in a book entitled De Revolutionibus Orbium Coelestium, it has been published that the heliocentric theory can overthrow the long-established geocentric theory. The Qur'an was revealed long before the astronomical concept of the earth's motion was put forward and was in line with the heliocentric view. In the Al-Qur'an, there are verses about the world, moon and sun, for example, Yunus: 5, al-Naml: 88, and Yasin: 38-40. The sun as the centre of the solar system is not static but also in motion. This is explained in the Al-Qur'an in Surah Yasin verses 38-40. Ahmad Mustafa al-Maraghi in Tafsir al-Maraghi emphasized that the heliocentric theory is by the Qur'an and the birth of the heliocentric idea is part of the miracle of al-Qur'an.